Penguatan Kapasitas Masyarakat Sebagai Mitra Program Keluarga Harapan di Kecamatan Muara Bangkahulu - Nopiah, Ririn; Ramah, Nabila Miftaahur; Putri, Gustina Adela; Rospida, Lela; Rambe, Roosemarina Anggraini; Azansyah (UNIB Press, 2025)
Poverty remains a major issue in national development, including in Bengkulu City. This community service activity aims to improve beneficiary families' understanding of the Program Keluarga Harapan (PKH), provide accurate information through the Social Services Agency, and encourage community participation in supporting poverty alleviation efforts. The method used in this community service activity is an interactive method combined with direct outreach by the Social Services Agency. This approach has proven effective because it increases participants' trust in the information provided. Based on the questionnaire results, there was an increase in understanding, especially regarding beneficiary obligations and the program's long-term goals. Participants also assessed the delivery method as clear, easy to understand, and relevant to daily life. Therefore, this activity is a strategic effort to increase the effectiveness of PKH implementation at the local level.